Improving Students’ Writing Skill Through Project Based Learning For EFLStudents - Arik Susanti; Nazhrotur Rofidah; Anis Trisusana; Pratiwi Retnaningdyah (Universitas Veteran Bangun Nusantara, 2020)
In the global era, EFL learners must master writing skill in order to communicate and covey their message. Project based learning is used to motivate them to be independent learner. It is expected that students will engage in writing process. The purpose is to investigate whether project based learning can improve the students’ writing ability. It was experimental research to compare between experimental and control group. The samples were 60 students of junior high school. The instrument is writing test. The data was analysed using SPSS. The result shows that the mean score of control class in post-test is 64.60 (SD = 10.87420) and the mean score of experimental class is 84.83 (SD = 10.19494). It means the p value is .00 or less than 0.05. It indicates that there is significant difference on students’ writing skill between experimental group and control group. The results of post-test in experimental class are higher than the control class. It also supported by Eta Squared value 0.48 or classified as large effect. It means that the use of project based learning gave positive effect towards students’ writing skill. It is recommended to use project based learning to improve the English skills. Keywords : Writing, Project Based Learning, Descriptive Text, and Mini Magazine